Application of Hybrid External Skeletal Fixation with Bone Tissue Engineering Techniques for Comminuted Fracture of the Proximal Radius in a Dog - Minji Bae; Byung-Jae Kang; Junhyung Kim (Animals)
A seven-month-old male Pomeranian presented with left forelimb lameness after a fall. Radiographic assessment confirmed proximal radial head and ulnar comminuted fracture. The initial surgical intervention involved the use of hybrid external skeletal fixation (ESF) to stabilize the radial head, concomitant with the application of a composite of bone morphogenetic protein type 2 (BMP-2)-loaded hydroxyapatite and gelatin microparticles at the fracture site. Although successful radial head healing was achieved, the ESF pinholes caused a defect in the proximal ulnar diaphysis. Subsequently, the ESF was removed, and a locking plate was applied in conjunction with the BMP-2-loaded collagen membrane to correct the radius defect. Clinical follow-up at 4.8 years postoperatively revealed a mildly decreased range of motion of the affected elbow joint, but no clinical symptoms such as lameness. Radiography revealed minimal degenerative changes and a radioulnar synostosis. Computed tomography revealed differences in the leg length and bone density. Gait analysis revealed that the left forelimb had a significant improvement in weight-bearing capacity based on weight distribution–peak vertical force metrics, compared with the right forelimb. Based on clinical outcomes, the combined application of hybrid ESF and bone tissue engineering techniques can be considered a feasible alternative treatment for radial head fractures.